Some phytochemicals and sugar contents of black mulberry (Morus nigra L.) genotypes from Simav District, Kütahya Province, Turkey - V. Okatan; M. A. Gündeşli; A. Yu. Melyanovskaya; O. V. Panfilova; N. G. Krasova (Труды по прикладной ботанике, генетике и селекции)
The purpose of this research was to determine the biochemical contents in black (Morus nigra L.) mulberry genotypes grown in Kütahya Province. Total soluble solids content, pH, titratable acidity, total phenolics, vitamin C, DPPH radical scavenging activity, and soluble sugars (fructose, glucose, and sucrose) of black mulberry genotypes were determined at the end of the study. The highest total phenolics value was detected in SIM02 (2995.16 mg GAE g-1). The SIM03 genotype had the highest vitamin C content of 31.34 mg 100 g-1. The study indicated that radical scavenging activity (DPPH) of 19.05 (SIM03) was the highest. In terms of the most valuable chemical composition, the SIM01, SIM02 and SIM03 genotypes can be suggested and used for future breeding reasons. It is desirable to take actions in Turkey to conduct an extensive conservation program for Morus nigra biodiversity.